K etimologiji indoevropskega geografskega termina: psl. *mor'e, lat. mare --- pide. *mor-i-(N.) - Furlan, Metka (Slavistična revija, 2011)
The article provides additional semantic and formal justification for the over-hundred-year-old Curtius' and Sonne's connection between the geographic neuter noun *mori- (CSl. *mor'e, Lat. mare ...) with the verbal root *mer- 'to be die'.
Keywords: besedotvorje; etimologija; etymology; geografska terminologija; gepgraphic terminology; leksika; lexicon; word formation